2017
DOI: 10.1056/nejmoa1612567
|View full text |Cite|
|
Sign up to set email alerts
|

IgG Endopeptidase in Highly Sensitized Patients Undergoing Transplantation

Abstract: IdeS reduced or eliminated donor-specific antibodies and permitted HLA-incompatible transplantation in 24 of 25 patients. (Funded by Hansa Medical; ClinicalTrials.gov numbers, NCT02224820 , NCT02426684 , and NCT02475551 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
224
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(228 citation statements)
references
References 29 publications
2
224
1
1
Order By: Relevance
“…48 In addition, a Streptococcus pyogenes –derived endopeptidase that degrades immunoglobulin G (IgG), thereby inhibiting complement-dependent cytotoxicity and antibody-dependent cellular cytotoxicity, was shown to reduce or eliminate DSAs, permitting HLA-incompatible renal transplantation in 24 of 25 patients. 49 These novel agents may soon contribute to the prevention/treatment of AMR in heart recipients.…”
Section: Immunosuppression: Advances and The Lack Thereofmentioning
confidence: 99%
“…48 In addition, a Streptococcus pyogenes –derived endopeptidase that degrades immunoglobulin G (IgG), thereby inhibiting complement-dependent cytotoxicity and antibody-dependent cellular cytotoxicity, was shown to reduce or eliminate DSAs, permitting HLA-incompatible renal transplantation in 24 of 25 patients. 49 These novel agents may soon contribute to the prevention/treatment of AMR in heart recipients.…”
Section: Immunosuppression: Advances and The Lack Thereofmentioning
confidence: 99%
“…The paper published in the New England Journal of Medicine describing the use of IgG endopeptidase for desensitization in kidney transplantation by Jordan et al (8) reported results from two separate phase 1-2 studies conducted in the United States and Sweden. The primary objective was to examine safety, and secondarily, it examined efficacy of IgG endopeptidase.…”
mentioning
confidence: 99%
“…2013-005417-13) in kidney transplantation patients. Furthermore, IdeS is currently being investigated in two ongoing phase II studies, both in kidney transplantation patients (45). Data on IdeS pharmacokinetics and pharmacodynamics profile have been collected as well as the safety profile of the enzyme.…”
Section: Discussionmentioning
confidence: 99%